(untitled) (Comprehensive Journal of Science, 2025)
One of the greatest threats to human existence is the inability to cope with water supply demands. The forward osmosis (FO) process has therefore provided an alternative for the purification of water. The merit of utilizing FO is due to the fact that it works at low or no hydraulic pressure. In the current study, cellulose acetate flat sheet membranes (CAFSM) were fabricated using 20 wt.% CA, 48.33% acetone, and 31.66% formamide and tested for the FO process. The effect of evaporation time during casting was investigated. The evaporation times used in CAFSM are 0, 30, 60, and 90 seconds. The water flux of the CAFSM was measured using a 0.5M NaCl feed solution with different draw solutions of 2M NaCl and 2M MgCl₂.. The highest water flux achieved is 2.04 L/m²/h with the CAFSM prepared at 90 seconds evaporation time and using 2M NaCl draw solution. CAFSM prepared at 60 seconds evaporation time showed the lowest value of water flux of 0.288 L/m²/h. Heat treatment at 90°C improved the water flux of the CAFSM to 4.345 L/m²/h.